p53 is required for etoposide-induced apoptosis of human embryonic stem cells - Grandela, C. (2008)
The molecular mechanisms controlling DNA-damage-induced apoptosis of human embryonic stem cells (hESC) are poorly understood. Here we investigate the role of p53 in etoposide-induced apoptosis. We show that p53 is constitutively expressed at high levels in the cytoplasm of hESC. Etoposide treatment results in a rapid and extensive induction of apoptosis and leads to a further increase in p53 and PUMA expression as well as Bax processing. p53 both translocates to the nucleus and associates with the mitochondria, accompanied by colocalization of Bax with Mcl1. hESC stably transduced with p53 shRNA display 80% reduction of endogenous p53 and exhibit an 80% reduction in etoposide-induced apoptosis accompanied by constitutive downregulation of Bax and an attenuated upregulation of PUMA. Our data further show that undifferentiated hESC that express Oct4 are much more sensitive to etoposide-induced apoptosis than their more differentiated progeny. Our study demonstrates that p53 is required for etoposide-induced apoptosis of hESC and reveals, at least in part, the molecular mechanism of DNA-damage-induced apoptosis in hESC.